Natural factors outweigh anthropogenic impact on aquatic phoD-harboring communities along Yangtze River basin - Lin Xu; Qian Mao; Chaonan Li; Bo Tu; Xiangzhen Li (Ecological Indicators)
The bacterial communities encoding alkaline phosphatase (phoD) gene (phoD-harboring communities hereafter), play essential roles in regulating organic phosphorus (P) mineralization in aquatic ecosystems. Like other microbial communities, the diversity and composition of these functional communities are influenced by environmental gradients generated by both natural factors (e.g., climate) and anthropogenic impacts. However, the relative importance of these factors in shaping aquatic phoD-harboring communities remains largely unknown, particularly at large spatial scales, challenging the management of ecosystem functions in aquatic environments. This study aimed to address this knowledge gap by collecting phoD amplicon sequence data along the Yangtze River basin. Our results demonstrated that natural factors were more influential than anthropogenic impacts in shaping aquatic phoD-harboring communities. Richness of aquatic phoD-harboring communities was positively correlated with mean annual precipitation and temperature and exhibited a unimodal relationship with elevation. Precipitation was the most influential factor, shaping richness, community composition, and assembly processes of these functional communities. Although anthropogenic impacts did not significantly affect richness, they notably altered community structure. Moderate levels of anthropogenic impact were associated with more complex co-occurrence networks. The relative abundance of Firmicutes emerged as a key predictor of anthropogenic P input. Our results have implications that further efforts aimed to mitigate anthropogenic impacts on aquatic ecosystems should prioritize the preservation of functional microbial communities diversity and composition, with particular attention to increasing the abundances of stress-resistant (e.g., species belonging to Firmicutes) taxa.